On some new integral inequalities concerning twice differentiable generalized relative semi-(m, h)-preinvex mappings - KASHURI, Artion; DU, Tingsong; LIKO, Rozana (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
The authors first present some integral inequalities for Gauss-Jacobi type quadrature formula involving generalized relative semi-(m, h)-preinvex mappings. And then, a new identity concerning twice differentiable mappings defined on m-invex set is derived. By using the notion of generalized relative semi-(m, h)- preinvexity and the obtained identity as an auxiliary result, some new estimates with respect to Hermite-Hadamard type inequalities via conformable fractional integrals are established. These new presented inequalities are also applied to construct inequalities for special means. Mathematics Subject Classification (2010): 26A51, 26A33, 26D07, 26D10, 26D15.